Beyond the bot: Chatgpt's influence on student learning - Ahmed Azmi; Ismail Maakip; Peter Voo Su Kiong; Nurul Hudani Mohd. Nawi; Dg Norizah Ag Kiflee @ Dzulkifli; Murnizam Halik; Sanen Marshall; Weı Boon Quah (Iowa State University, 2024)
Given the widespread use of ChatGPT among university students, questions arise about its potential benefits and drawbacks. This study aims to explore the challenges and impacts of ChatGPT on the future of higher education. Using qualitative research methods, data were collected from semi-structured interviews. A thematic analysis approach was employed. Findings revealed that most students learned about ChatGPT primarily through social media, followed by friends and lecturers. While students acknowledged ChatGPT's ability to simplify and filter information, aiding in their understanding of topics, they also expressed concerns about increased dependency, potential laziness, and a decline in writing and critical thinking skills. Furthermore, students felt that ChatGPT could not replace higher education or lecturers due to its lack of emotional understanding. They also emphasized the impracticality of banning its use. Instead, they suggested that universities should explore ways to regulate its use, with specific recommendations discussed in the article. Lastly, students recognized the importance of learning to use ChatGPT, citing potential job requirements and their utility in assisting with assignments and learning.